THE ROLE OF FINANCIAL INSTITUTIONS IN INDIAN ECONOMIC STABILITY (International Journal of Food and Nutritional Sciences, 2023)
Financial institutions play a pivotal role in ensuring economic stability in India by acting as intermediaries that facilitate the mobilization and allocation of resources. These institutions, which include banks, non-banking financial companies (NBFCs), insurance firms, and capital market entities, contribute significantly to the overall health of the economy. By promoting savings and investments, they provide the necessary capital for businesses and households, thereby stimulating economic growth and employment. One of the essential functions of financial institutions is risk management, where they help mitigate financial volatility through prudent lending practices and effective regulation. The Reserve Bank of India (RBI), as the central bank, oversees monetary policies that manage inflation and interest rates, crucial for maintaining economic equilibrium. Moreover, financial institutions promote financial inclusion by extending services to marginalized populations, empowering individuals and communities to participate in the economy. This inclusivity enhances consumption, investment, and productivity, further bolstering economic stability.